Vulnerabilidade em saúde de adolescentes na região de fronteira - Corrêa, Rafael Soares (2017)
The study characterizes the health vulnerability conditions of adolescents from a border region. Cross section developed in the city of Foz de Iguaçu with students from the public high school and technical education network. The sample consisted of 722 participants from 15 to 17 years of age, being 46.30% male and 53.70% female. The drawing consisted of a probabilistic sample of conglomerates and simple random, carried out in 29 colleges and 40 classrooms. Data analysis was performed from descriptive statistics and association of factors such as alcohol use, cigarette smoking, illicit drugs, sexual vulnerability, and bullying through binary analyzes using chi-square test and multiple logistic regression. In the prevalence investigation, the following percentages were observed for males and females: alcohol use, 52.7% and 44.4%; Tobacco use, 10.8% and 5.45%; Use of illicit drugs, 7.8% and 3.9%; Episodes of bullying among adolescents, 18.6% and 16.2%; Sexual vulnerability, measured by adolescents who had sexual intercourse before 14 years of age and without protection, 15.3% and 9%. The correlation between bullying and sexual vulnerability with sociodemographic characteristics, alcohol consumption, smoking and illicit drugs occurred with a higher probability for adolescents who used alcohol before the age of 14 years (p 0.016), who used marijuana in the last month (p 0.006) (P 0.010), who used cigarettes before age 14 (p 0.019), had crack use in the last month (p 0.001), and had friends who used drugs (p 0.005). These factors require greater attention in adolescent health in the border region involving strategic and planned intersectoral interventions involving various actors in society.